O uso do referencial teórico em teses de doutorado na área da ciência da informação: uma análise à luz da contribuição de pensadores selecionados - COSTA, Marcos Oliveira da (2017)
It discusses the importance of the theoretical framework as the basic phase inherent to the development of academic work, based on the theoretical and theoretical concepts pointed out by the study. It aims to study the characteristics related to the theoretical framework through the creation of a theoretical-methodological index to better understand the meaning of the same and the theoretical contributions necessary for its construction, as well as to contribute in the construction of academic work in Librarianship and Information Science. On the methodological pathways, the nature of the research is applied, its definition fits as exploratory and descriptive research, the character of the study is qualitative and the selected data collection instrument was the bibliographical survey and the method used was the inductive method. For the construction of the index an analysis was made in the doctoral theses of the courses of Information Science of UNESP Campus Marília and UFMG, both universities were chosen because they were the best evaluated in the last triennial evaluation made by CAPES. After analyzing the results it can be observed that not all authors are configured as theoreticians and that the process of development of the theoretical framework requires theoretical paradigms. Based on the aforementioned results it was concluded that the theoretical framework is composed of a set of related steps and that the choice of theorists and theories are of paramount importance in its construction with the objective of supporting and guiding all stages related to work academic.